Digital Marketing Training on MSMEs Built by BPODT (Lake Toba Authority Implementing Agency) - Melia, Yona; Rafika, Mulya; Arjuna, Syukron; Siregar, Muhammad Raja; Limbong, Christine Herawati (CV. Inara, 2022)
Information technology that is developing rapidly can be beneficial for the community in supporting various business activities, both large and small scale businesses, including the activities of Micro, Small and Medium Enterprises (UMKM) so that they can be marketed globally. This activity aims to improve and develop digital marketing which is one of the digital-based product and service marketing techniques carried out by various Micro, Small and Medium Enterprises (UMKM) in the Lake Toba Caldera village. In this study, we describe the impact of digital marketing on sales volume for UMKM actors in the Caldera village. The method used in this research is descriptive qualitative research, namely research methods that are focused on problems based on facts which are carried out by means of observation, interviews and studying documents. The data analysis technique used is descriptive analysis, the results of research in the Caldera village are known.